Imaginable as other The Representation of Muslims in Zaide and Zaide’s Philippine History of Government and Agoncillo’s History of the Filipino People - REILLY, BRANDON (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper looks at the tendency of Filipino national histories to represent Filipino Muslims as Other, rather depicting them as constituent members of the nation. These narratives help to perpetuate the cultural misunderstandings that characterize Christian-Muslim relations and they ultimately postpone the meaningful integration of Muslims into the body politic. I demonstrate how two archetypical examples of the genre: Zaide and Zaide’s Philippine History and Government and Agoncillo’s History of the Filipino People, misrepresent, downplay, or at points even denigrate Moro contributions to national history. My hope is that by rendering visible the problematic representations of Muslim Filipinos, we can begin the process of revising Filipino history so that it is more inclusive and appreciative of all of its minority and marginalized groups.